The International Justice Between Humanitarianism and Global Egalitarianism (Andamios, Revista de Investigación Social, 2014)
When it comes to international justice, a central question in theories of justice discussions refers to the appropriate normative perspective to deal with large disparities in life perspectives in the world at large. It remains a controversial issue whether these disparities should be tackled with principles of egalitarian justice, as authors such as Simon Caney and Kok-Chor Tan argue, or, as it is argued by authors such as John Rawls, David Miller and Thomas Nagel, whether a principle of humanitarianism is the appropriate normative response. This article argues that, though a conception of global egalitarian justice does not qualify as a “realistic utopia”, the existing political and socioeconomic order triggers rules of (noncomparative) justice that go beyond humanitarianism.
Keywords: International justice; social justice; social liberalism; global egalitarianism; Human Rights